2005
DOI: 10.1007/s10750-004-7134-7
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial trends in heavy metal concentrations in the marine mussel Mytilus edulis from the Western Scheldt estuary (The Netherlands)

Abstract: Since the first North Sea Conference (1984, Bremen), all countries bordering the North Sea made commitments to reduce discharge of hazardous substances into the North Sea. From Belgium and The Netherlands, large reductions (upto 90%) in heavy metal emissions from land-based sources have been reported between 1985 and 2000. Recently, some studies in the Western Scheldt estuary (WS) have shown that total metal concentration in the water, sediments and suspended particles have decreased compared to levels in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 48 publications
5
16
1
3
Order By: Relevance
“…Only Zn showed similarity to the results obtained in the present work (Vernocchi et al, 2007). Higher concentrations in colder months were also identified by Mubiana et al (2005) for M. edulis in the Netherlands, with Cd, Cr, Zn in the winter, and Fe, Mn, Ni, and Pb in the spring; the values for Mn and Ni are corroborated by those observed in the present work.…”
Section: Resultssupporting
confidence: 92%
“…Only Zn showed similarity to the results obtained in the present work (Vernocchi et al, 2007). Higher concentrations in colder months were also identified by Mubiana et al (2005) for M. edulis in the Netherlands, with Cd, Cr, Zn in the winter, and Fe, Mn, Ni, and Pb in the spring; the values for Mn and Ni are corroborated by those observed in the present work.…”
Section: Resultssupporting
confidence: 92%
“…Mean Cd levels in all invertebrates from False Bay were greater than those found by Greenfield et al (2011) for Perna perna and Liu & Kueh (2005) for Perna viridus in Victoria Harbour, Hong Kong. However, all the maximum concentrations we measured in mussels from False Bay were below the metal concentrations recorded for mussels (Mytilus edulis) from the metal polluted Western Scheldt Estuary in The Netherlands (Mubiana et al 2005).…”
Section: Discussioncontrasting
confidence: 73%
“…1) to obtain baseline information of Cd levels in intertidal invertebrates and their immediate surroundings. Seasonal effects are also critical in biomonitoring programmes (Mubiana et al 2005). However, little is known about the influence of seasonal changes on metal content in organisms of the intertidal zone in False Bay.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that accumulated trace metals concentrations in bivalves vary significantly with season and body size (Casas et al 2004;Lobel and Wright 1982;Wallace et al 2003;Mubiana et al 2005), which occasionally requires correcting these effects before spatial comparisons are made on large scales. However, the influence of an animal's size (age) on soft tissue metal concentration appears to be ambiguous and can depend on local environmental conditions.…”
Section: Introductionmentioning
confidence: 99%